Hubungan Antara Kecerdasan Hati, Motivasi Diri, dan Kekuatan Daya Ingat dengan Prestasi Belajar Mahasiswa Prodi Keperawatan Universitas Timor - Pius A.L Berek; Maria Fatimah W. A Fouk; Rufina Nenitryana; Handrianus Akoit (Jurnal Nirta : Inovasi Multidisiplin, 2024)
Abstract. Learning achievement is an indicator of academic success that is influenced by various factors such as spiritual intelligence, self-motivation, and memory ability. This study aims to analyze the relationship between intelligence, self-motivation, and memory ability with learning achievement of nursing students at Timor University. The study design used a cross-sectional approach with a sample of 130 students selected purposively. Data were collected using a standard questionnaire related to Spiritual Intelligence, self-motivation, and memory ability and GPA as an indicator of learning achievement. Data were analyzed using the Pearson correlation test (p < 0.05). The results showed that there was no significant relationship between spiritual intelligence, self-motivation, and memory ability with learning achievement (p-value > 0.05). This finding indicates that these three factors are not the main determinants of academic success.